A six-week inspiratory muscle training and aerobic exercise improves respiratory muscle strength and exercise capacity in lung cancer patients after video-assisted thoracoscopic surgery: A randomized controlled trial. (June 2021) - Liu, Jui-Fang; Kuo, Nai-Ying; Fang, Teng-Pei; Chen, Jui-O; Lu, Hung-I; Lin, Hui-Ling
Objective: To compare the postoperative outcomes of inspiratory muscle training and aerobic exercise, along with standard care, on lung cancer patients undergoing video-assisted thoracoscopic surgery (VATS). Design: A parallel-group, single-blind randomized clinical trial Setting: Thoracic surgery ward and outpatient clinic in a teaching hospital Subjects: Overall 63 patients underwent VATS were randomly assigned to a triaging (TG, n =  32) or control group (CG, n =  31). A total of 54 patients (TG, n =  26; CG, n =  28) completed the study. Intervention: TG: six-week threshold inspiratory muscle training and aerobic exercise. CG: standard care. Main measures: Maximum inspiratory pressure (PImax), maximum expiratory pressure (PEmax) lung expansion volume, and 6-min walking test (6MWT) were performed on the day of chest tube removal (baseline), and 2, 6, and 12 weeks postoperatively. Results: The TG showed significant improvement in PImax at week 6 (71.6 ± 34.9 vs. 94.3 ± 32.8 cmH2 O, P  = 0.018), PEmax at week 2 (70.9 ± 24.3 vs. 90.9 ± 28.2 cmH2 O, P  = 0.015) and week 12 (76.1 ± 20.2 vs. 98.6 ± 35.3 cmH2 O, P  = 0.012), the lung expansion volume at week 2 (1080 ± 433 vs 1457 ± 624 mL, P  = 0.02) and week 12 (1200 ± 387 vs 1885 ± 678 mL, P  < 0.001), in addition to the 6MWT at week 2 (332 ± 78 vs 412 ± 74 m, P  = 0.002), week 6 (360 ± 70 vs 419 ± 60 m, P  = 0.007) and week 12 (360 ± 58 vs 402 ± 65 m, P  = 0.036). Conclusion: A six weeks of inspiratory muscle training and aerobic exercise had improved respiratory muscle strength and aerobic exercise postoperatively in lung cancer patients after VATS as early as 2 weeks.